Studies of income distribution functions in econophysics using particle swarm optimization - Santos, Paulo Henrique dos (2025)
Tese (doutorado) - Universidade Federal de Santa Catarina, Centro de Ciências Físicas e Matemáticas, Programa de Pós-Graduação em Física, Florianópolis, 2025.